2020
DOI: 10.1177/1359104520963372
|View full text |Cite
|
Sign up to set email alerts
|

A psychological support group for parents in the care of families with gender diverse children and adolescents

Abstract: Parenting gender diverse children and adolescents can be a challenging experience, entailing doubts about how to protect and support them during their development. Parental reactions impact on the child’s sense of security and well-being. Therefore, when caring for families with gender diverse children, it is important to offer support to parents. In this article we present an experience with a 12-month support group for parents of young people who attended the service for gender identity development at a paed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 19 publications
(30 reference statements)
0
32
0
5
Order By: Relevance
“…Also, increasing the presence of support groups for parents is important. In fact, the role of support groups for parents is widely highlighted in literature, in particular as a means for advocacy (see also, Caldarera, Davidson, Vitiello, & Baietto, 2021; Pickett, Heller, & Cook, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Also, increasing the presence of support groups for parents is important. In fact, the role of support groups for parents is widely highlighted in literature, in particular as a means for advocacy (see also, Caldarera, Davidson, Vitiello, & Baietto, 2021; Pickett, Heller, & Cook, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The articles were published in 2009 (3.5%) [ 17 ], 2011 (3.5%) [ 18 ], 2013 (3.5%) [ 19 ], 2014 (7.1%) [ 20 , 21 ], 2015 (3.5%) [ 22 ], 2016 (7.1%) [ 23 , 24 ], 2018 (7.1%) [ 25 , 26 ], 2019 (17.8%) [ 27 , 28 , 29 , 30 , 31 ], 2020 (17.8%) [ 32 , 33 , 34 , 35 , 36 ], and 2021 (28.5%) [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. All articles (100%) were published in English, of which 17 (60.7%) [ 17 , 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 32 , 33 , 34 , 35 , 37 , 40 , 44 ] originated in America, 3 (32.1%) [ 20 , 30 , 31 , 35 , 36 , 37 , 38 , 39 , 41 , ...…”
Section: Resultsmentioning
confidence: 99%
“…The methodological quality of the articles included in the final sample of this review was assessed and they all showed congruence in the following aspects: philosophical perspective and research methodology; research methodology and research question or objectives; research methodology and data collection methods; participants and their voices adequately represented; compliance with ethical issues and conclusions of data analysis or interpretation [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…These discussions are relevant because, a lot of times, organizations have institutionalized cisnormativity, which makes the trans individual vulnerable to marginalization and discrimination [119]. The importance of psychological support for parents of children and adolescents of different genders is also discussed, so they can strengthen the processes of communication and acceptance of their children [122].…”
Section: Analysis and Discussion Of The Fourth Subperiod (2011-2021)mentioning
confidence: 99%